Trash Talking in Virtual Communication: A Study of Community Symbolic Interactions Game Online Pubg Mobile Nostra Bone - Rosniar, Rosniar; Syam, Syahrianti; Wardana, Dimas Alfareza (State Islamic Institute of Bone, Indonesia, 2023)
This research discusses communication behaviortrash talking what happens insidegame online PUBG Mobile through virtual communication features vizchat and voice chat which allows users to interact with other players. This research aims to analyze behavior trash talking Nostra Bone teenager in play game online PUBG mobile. The type of research used is descriptive qualitative. Primary data was obtained based on the results of observations and interviews with the Nostra Bone youth group, a community game online PUBG Mobile in Bone Regency, South Sulawesi Province. Research shows that behavior trash talking what Nostra Bone teenagers do when playing game online PUBG Mobile, namely the motivation and duration of playing PUBG Mobile which varies depending on each player's preferences, use of features chat and voice chat which is used to communicate virtually between players, and trash talking when playing PUBG mobile, it takes the form of aggressive communication carried out by players, among others flaming, that is, send chat and voice chat which is offensive in nature in the form of using harsh words, insulting or degrading other players.